DAMPAK BENCANA ALAM TERHADAP POTENSI EKONOMI INDONESIA - Nurhasan Syah; Widya Prarikeslan (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
Abstrak Different approach by evaluating the specific impact on the economy. Evaluation of economic impact of extreme natural events that provide a measure of the costs of the impact of extreme natural events to the public. The magnitude of natural disasters can be assessed physically, socially, or economically. Response to losses in action packed form of both structural and non-structural adjustment so expect such losses can be minimized level in anticipation or immediately.